Factors affecting the outcome of neonatal transport in a tertiary care hospital in Bangladesh - Akhter, Mohosina; Pervez, Mehdi; Sultana, Shahjadi Nasreen; Haque, Mahbuba; Abdul Kadir, M.; Bhuiyan, Mohammad Faisal Hasan; Saha, Uttam Kumar (International Journal of Contemporary Pediatrics, 2025)
Background: Effective neonatal transport is crucial for survival of referred sick newborns and poor transportation is associated with higher mortality. In Bangladesh many births still occur at home, especially in rural areas and newborn transport system is not established contributing to adverse neonatal outcome. This study aimed to document the factors affecting the outcome of transport of sick neonates to a tertiary care hospital. Methods: This prospective observational study was conducted at Department of Neonatology in Mymensingh Medical College Hospital over a period of 6 month extending from January 2023 to June 2023. Neonates were enrolled if referred within 28 days of life and excluded if they had major congenital anomalies. Data on pre-transport, during-transport and post-transport conditions were recorded using a structured questionnaire. Outcomes were categorized as uneventful or complicated transfers, with survival analyzed as a secondary outcome. Statistical analysis was performed using SPSS, with chi-square tests to assess associations (p<0.05). Results: Out of 384 referred neonates included in this study, 124 (32.3%) had uneventful transfer and 260 (67.7%) had complicated transfers. Prematurity, low birth weight, home delivery, delivery by untrained dai, self-referral, no prereferral treatment and counselling, lack of accompanying health personnel during transport, higher distance, transport without ambulance, lack of adequate support and monitoring equipment and treatment during transport was significantly associated with complicated transport (p<0.05). Mortality was significantly higher in complicated transport group (38.9%) compared to uneventful transport (26.6%). Conclusions: In conclusion, this study highlights significant gaps in neonatal transport practices revealing that both pre-transport and transport conditions critically influence outcomes. The findings underscore the urgent need for a specialized neonatal transport service to reduce neonatal mortality and morbidity.